2006
DOI: 10.1016/j.jembe.2006.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant responses and lipid peroxidation in gills and erythrocytes of fish (Rhabdosarga sarba) upon exposure to Chattonella marina and hydrogen peroxide: Implications on the cause of fish kills

Abstract: Chattonella marina, a red tide or harmful algal bloom species, has caused mass fish kills and serious economic loss worldwide, and yet its toxic actions remain highly controversial. Previous studies have shown that this species is able to produce reactive oxygen species (ROS), and therefore postulated that ROS are the causative agents of fish kills. The present study investigates antioxidant responses and lipid peroxidation in gills and erythrocytes of fish (Rhabdosarga sarba) upon exposure to C. marina, compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 76 publications
(106 reference statements)
3
22
2
Order By: Relevance
“…They proposed that when C. polykrikoides passed through the fish gill lamella, gill cells were attacked by the ROS generated by algal cells, resulting in an oxidative damage. In the present work, the concentration of H 2 O 2 measured in the F. japonica tanks were not considerably higher than in those with the non-toxic diatom P. tricornutum and since the compound alone was not toxic for the fish, even when added at high concentrations, this result confirms that other factors are likely to be involved in the toxic mechanism, as already suggested for C. marina (Marshall et al, 2003;Woo et al, 2006).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…They proposed that when C. polykrikoides passed through the fish gill lamella, gill cells were attacked by the ROS generated by algal cells, resulting in an oxidative damage. In the present work, the concentration of H 2 O 2 measured in the F. japonica tanks were not considerably higher than in those with the non-toxic diatom P. tricornutum and since the compound alone was not toxic for the fish, even when added at high concentrations, this result confirms that other factors are likely to be involved in the toxic mechanism, as already suggested for C. marina (Marshall et al, 2003;Woo et al, 2006).…”
Section: Discussionsupporting
confidence: 90%
“…MDA is the major aldehyde formed upon breakdown of lipid hydroperoxides and is still the most commonly applied assay for oxidative stress (Seljeskos et al, 2006); in fact, ROS can react with the double bonds of PUFAs to yield lipid hydroperoxides and one of the major secondary oxidation products is MDA. The average MDA concentrations measured in the gills of fish exposed to F. japonica were 13-14-fold higher than those of the controls, in contrast to the results obtained by Woo et al (2006) in goldlined seabream exposed to C. marina for a period up to 6 h. We had also observed that fish exposed to F. japonica for 5 days without reporting mortality, then being kept in seawater for 2-4 weeks and exposed for the second time to F. japonica, died within a shorter time period (6-8 days) (data not shown). This fact leads us to postulate the involvement in fish mortality of a permanent and accumulating damage, such as the one caused by organ impairment, but to exclude an acute effect such as the one resulting, for example, from red blood haemolysis.…”
Section: Discussioncontrasting
confidence: 87%
“…Baden (1989) and Plakas et al (2002) noted that brevetoxins are lipid-soluble polyether molecules that are readily accumulated and metabolized by bivalves. Furthermore, neither laboratory nor field data indicate that agents toxic to fish (such as brevetoxins or ROS) can be produced in sufficiently high levels during Chattonella blooms to cause fish gill damage or fish mortality (Tang et al 2005, Woo et al 2006. Thus, our observations support the conclusions reported by previous studies that Chattonella toxins (such as brevetoxins and ROS) have little effect on fish and bivalve mortality (Baden 1989, Plakas et al 2002, Tang et al 2005, Woo et al 2006.…”
Section: Discussioncontrasting
confidence: 51%
“…ROS production can be insufficient to produce oxidative damage since there was a lack of antioxidant enzyme response particularly at least during acute duration and Cd exposure in this study. Similarly, Woo et al (2006) observed neither significant changes in antioxidant enzymes nor lipid peroxidation in fish Rhabdosarga sarba upon exposure to toxicants. In addition, Roche and Boge (1996) observed unchanged SOD and CAT activities in the red blood cell of sea bass Dicentrarchus labrax after Cu exposure, though increases and decreases were also observed after Cr and Zn exposures.…”
Section: Antioxidant Enzyme Activitiesmentioning
confidence: 76%